Notes on the orchids of Gunung Telapak Buruk, Hutan Simpan Berembun, Negeri Sembilan - Farah Alia, Nordin; Rahmad, Zakaria; Mohd Faizal, Azmi; Mohd Azlan, Azmi; Mohd Akmal, Mohd Raffi; Hardy Chin, Adrian A. (Jabatan Perhutanan Negeri Sembilan, 2024)
A total of 71 species of orchids was recorded from the Gunung Telapak Buruk, Rutan Simpan Berembun and summit area that consisted of the common montane forests species. The discovery of a rare species of jewel orchid from genus Anoectochilus Blume is much compelling - the species identification remains dubious; thus, further taxonomic inquiry is crucially needed.